Unveiled one woman's nightmare in Iran / Cherry Mosteshar - Mosteshar, Cherry (1995)
This is Cherry's true story--from her arrival into a monstrous marriage where she became just one of her husband's wives, to her harrowing years as a victim of his sexual whims and his violent outbursts, to her heroic struggle to maintain her identiy while a prisoner stripped of all rights and dignity, to her plight as a terrified victim ready to do anything to save her own life and escape...